Rights management in digitization projects: public domain and orphan works - Maria Cassella (JLIS.it, 2013)
The essay is dedicated to the theme of digital rights management on digitisation projects with particular reference to works into the public domain and to orphan works. The aim of the essay is to explain the main issues and criticalities that libraries have to face proposing and carrying out digitisation projects. For some years, the digitisation of cultural heritage involves libraries, archives and museums and is one of the main goals by the Digital Agenda for Europe. Indeed the digitisation is one essential tool to broaden the accessibility to the cultural heritage of Europe and to promote the growth. As a part of this context, the essay highlights the legal issues related to the process of digitization of cultural heritage for works into the public domain and for orphan works.